دور حاضنات الأعمال في توجيه الطلبة نحو ريادة الأعمال في الجامعات الجزائرية - فقير، صابرين (University Of Eloued جامعة الوادي, 2025)
هدفت هذه الدراسة إلى تسليط الضوء على الدور الذي تلعبه حاضنات الأعمال في تحقيق التوجه نحو ريادة الأعمال في البيئة الجامعية الجزائرية، حيث انصب تركيزنا على آليات الدعم والمرافقة التي تعتمدها هذه الأخيرة لإنجاح الأفكار المحتضنة وبعثها إلى مشاريع منتجة قادرة على النمو والاستمرار، وكذا التعرف على نية التوجه الريادي لدى الطلبة المحتضنين داخل حاضنات الأعمال الجامعية الجزائرية محل الدراسة حاضنة أعمال جامعة المسيلة حاضنة أعمال جامعة الوادي حاضنة أعمال جامعة ورقلة، ولتحقيق أهداف الدراسة استخدمنا المنهج الوصفي لوصف الوضع القائم من خلال عرض أهم العناصر التي توضح كل ما يتعلق بحاضنات الأعمال والتوجه الريادي والمنهج التحليلي لتفسير العلاقة بين أبعاد متغيرات الدراسة حاضنات الأعمال الجامعية التوجه الريادي)، حيث تم استخدام الاستبانة كأداة رئيسية لجمع البيانات حول الظاهرة المدروسة، وتم توجيهها إلى عينة مكونة من (153) مفردة، وبعد إجراء المعالجة الإحصائية ومناقشة النتائج وتحليلها خلصت الدراسة إلى وجود علاقة طردية قوية بين دور حاضنات الأعمال الجامعية والتوجه الريادي للطلبة الجامعيين، إضافة إلى وجود أثر معنوي قوي ذو دلالة إحصائية بين كل أبعاد حاضنات الأعمال الجامعية ينتج عنه تحقيق التوجه نحو ريادة الأعمال، كما توصلنا إلى أن حاضنات الأعمال الجامعية الجزائرية محل الدراسة تحتوي على كوادر بشرية تسهم في مرافقة المنتسبين لها بتقديم تشكيلة متنوعة من الخدمات إلا أنها لا تساهم في عملية التمويل المادي للمشاريع، وهذا من أبرز الأسباب التي تعرقل دورها، حيث يقتصر على أنها عبارة عن هياكل مهيأة للمرافقة، وبالتالي يجب على الهيئات المعنية إعطاء صلاحيات أكثر لهذه الحاضنات حتى تتمكن من لعب الدور المنوط لها بشكل فعال. Abstract: This study aims to highlight the role that business incubators play in fostering entrepreneurial orientation within the Algerian university environment. The focus is on the support and mentoring mechanisms that these incubators employ to ensure the success of incubated ideas and their development into productive, sustainable projects. Additionally, the study seeks to understand the entrepreneurial intentions of students within the university business incubators under study (the business incubators of M'sila University , El Oued University and Ouargla University). To achieve the study's objectives, we employed the descriptive method to outline the existing situation by presenting key elements related to business incubators and entrepreneurial orientation. The analytical method was used to interpret the relationship between the study's variables (university business incubators and entrepreneurial orientation). A questionnaire was used as the primary tool for data collection, targeting a sample of 153 individuals. After conducting statistical analysis and discussing the results, the study concluded that there is a strong positive relationship between the role of university business incubators and the entrepreneurial orientation of university students. Additionally, there is a significant and statistically meaningful impact of all dimensions of university business incubators in fostering entrepreneurial orientation. The study also found that the Algerian university business incubators under study have qualified personnel who assist their affiliates by providing a variety of services, yet they do not contribute to the financial funding of projects. This is one of the main obstacles hindering their role, as they function primarily as support structures. Therefore, relevant authorities should grant more powers to these incubators to enable them to effectively fulfill their intended role.
Thesis
Keywords: حاضنات الأعمال الجامعية; مشاريع ناشئة; ابتكار; تحمل المخاطرة; university business incubators; entrepreneurial orientation; start-up projects; innovation; risk-taking